Anti-Inflammatory Cytokine Interleukin-4 Inhibits Inducible Nitric Oxide Synthase Gene Expression in the Mouse Macrophage Cell Line RAW264.7 through the Repression of Octamer-Dependent Transcription. (29th December 2013) - Hiroi, Miki; Sakaeda, Yoshiichi; Yamaguchi, Hana; Ohmori, Yoshihiro
Abstract : Inducible nitric oxide synthase (iNOS) is a signature molecule involved in the classical activation of M1 macrophages and is induced by the Nos2 gene upon stimulation with Th1-cell derived interferon-gamma (IFN γ ) and bacterial lipopolysaccharide (LPS). Although the anti-inflammatory cytokine IL-4 is known to inhibit Nos2 gene expression, the molecular mechanism involved in the negative regulation of Nos2 by IL-4 remains to be fully elucidated. In the present study, we investigated the mechanism of IL-4-mediated Nos2 transcriptional repression in the mouse macrophage-like cell line RAW264.7. Signal transducer and activator of transcription 6 (Stat6) knockdown by siRNA abolished the IL-4-mediated inhibition of Nos2 induced by IFN γ /LPS. Transient transfection of a luciferase reporter gene containing the 5′-flanking region of the Nos2 gene demonstrated that an octamer transcription factor (OCT) binding site in the promoter region is required for both positive regulation by IFN γ /LPS and negative regulation by IL-4. Although IL-4 had no inhibitory effect on the DNA-binding activity of constitutively expressed Oct-1, IL-4-induced Nos2 -reporter transcriptional repression was partially attenuated by overexpression of the coactivator CREB-binding protein (CBP). These results suggest that a coactivator/cofactor that functionally interacts with Oct-1 is a molecular target for the IL-4-mediated inhibition of Nos2 and that IL-4-activated Stat6 represses Oct-1-dependent transcription by competing with this coactivator/cofactor.